Measuring poverty of province of Java using micro data, are the results the same as macro data? - Amrina, Dania Hellin; Badri, Ferdian; Umaroh, Rodhiah; Udjianto, Didit Welly (Optimum: Jurnal Ekonomi dan Pembangunan, 2025)
Poverty is a problem that still occurs in many countries, both developed and developing countries. One of the important pieces of information from using microdata is to provide a map of the characteristics of the target households. Characteristics of poor households obtained through analysis of micro poverty data. The data used in this study is IFLS (Indonesian Family Life Survey) 5 data using data from the Provinces of DI Yogyakarta, West Java, Central Java, East Java, DKI Jakarta, and Banten. The variables used are characteristic variables from the Multidimensional Poverty Index (MPI) indicators, namely household health, health insurance, school level, and quality of household life in the form of sanitation, drinking water, electricity, cooking fuel, vehicles, electronics, and savings. This study found that there are differences in poverty calculated by applying monetary and multidimensional poverty. This research shows that monetary (consumption) alone is not enough to explain the deprivation faced by the poor. The low level of education, health, and household quality in the form of drinking water is a concern for the government to evaluate existing programs and policies.